Computer-assisted instruction at Stanford, 1966-68 data, models, and evaluation of the arithmetic programs - Suppes, Patrick, 1922-2014; Morningstar, Mona (Academic Press, 1972)
Computer-Assisted Instruction at Stanford, 1966-68.